(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the didactic work of the great Uzbek enlightener Abdulla Avloniy “The Turkic Flower Garden, or Moral”. This work contains invaluable ideas about the moral education of children. The author of the article reflects on the role and importance of this work in the process of educating today’s youth based on Eastern traditions and moral heritage.